PRISONERS OF WAR LEGAL REGIME IN RUSSIA-UKRAINE CONFLICT - Gushchyn, O.; Kyryshun, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article examines the content of the legal regime defined by the Third Geneva Convention of 1949 and the First Additional Protocol of 1977 regarding the treatment of prisoners of war. The content of the obligations of the subjects of international relations for the implementation of the norms and principles of IHL was studied. The results of the implementation activities of Ukraine and the Russian Federation before the start of full-scale aggression and after it were analyzed. Attention is paid to the importance of researching the content of the updated 2020 Commentary to the Third Geneva Convention and its implementation into national legislation. The content of the main principles of International Humanitarian Law regarding the treatment of prisoners of war is described in detail. It is noted that the level of effectiveness of compliance with the norms and principles of IHL during the conflict depends on the completeness of the implementation. As of February 2022, both states were not ready to fulfill their obligations to comply with GCIII. Ukraine, as a party to the conflict, quickly began implementation activities and adopted a number of acts on the treatment of prisoners of war, including a national information bureau. On the other hand, the Russian Federation did not and still does not intend to initiate similar implementation measures. The problem of the procedure of activating the legal regimes "state of war" and "martial law" by political leadership of Ukraine, as well as the formal recognition of the existence of an international armed conflict, is considered. The National Information Bureau in Ukraine was created and started its activities. In Russia internal legal and political discourse still does not recognize the existence of an armed conflict which hinders the implementation process.